2022
DOI: 10.1155/2022/2562872
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Shale-Reservoir Rocks Based on Stress–Strain Curves and Mineral Content

Abstract: The evaluation of rock mechanic characteristics of shale reservoir is the key for the success of fracturing. Several limitations such as complex lithology can affect the accuracy of the rock mechanic property computation. In this research, the mechanical rock properties of shale reservoirs were analyzed based on experimental tests including shale-reservoir mineral composition, uniaxial compressive strength, and triaxial compression tests. The results showed that (1) the difference in mineral composition leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Through uniaxial compression test, they found that the difference in the mechanical properties of coal and oil shale affected the stress state near the interface, resulting in the increase in coal strength and the decrease in oil shale strength. Sun et al [15] found that, based on mineral composition, the uniaxial compressive strength and triaxial compression tests of shale reservoir, it was found that the mechanical properties of the shale reservoir in parallel bedding direction are less affected by lithology under uniaxial conditions. There is an increase in the compressive strength of rock, with a higher confinement in triaxial tests.…”
Section: Introductionmentioning
confidence: 99%
“…Through uniaxial compression test, they found that the difference in the mechanical properties of coal and oil shale affected the stress state near the interface, resulting in the increase in coal strength and the decrease in oil shale strength. Sun et al [15] found that, based on mineral composition, the uniaxial compressive strength and triaxial compression tests of shale reservoir, it was found that the mechanical properties of the shale reservoir in parallel bedding direction are less affected by lithology under uniaxial conditions. There is an increase in the compressive strength of rock, with a higher confinement in triaxial tests.…”
Section: Introductionmentioning
confidence: 99%